Analisis Kebutuhan Guru terhadap Bahan Ajar Interaktif IPAS Berbasis Tri Hita Karana di Sekolah Dasar Negeri 2 Batur - I Nyoman Sudirman; I Wayan Anto Wijaya (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to develop Natural and Social Sciences (IPAS) learning articles with a Tri Hita Karana orientation to increase teachers' needs for interactive teaching materials at SD Negeri 2 Batur. In the independent curriculum, science and social studies learning is combined into Natural and Social Sciences (IPAS) subjects, with the hope that teachers can fulfill learning needs. The approach used in this research is descriptive qualitative, with the research subjects consisting of science and technology teachers. The techniques used in data collection were carried out through in-depth interviews and observation. The research results show that teachers need teaching materials that are more interactive, relevant to the local context, and able to integrate Tri Hita Karana values ​​in learning. The main challenges faced are limited technological facilities and a lack of teaching materials that link science concepts to students' daily lives. Based on research results, the development of local wisdom-based teaching materials such as Tri Hita Karana has the potential to increase students' active participation and support learning that is more meaningful, effective and relevant to the cultural context and local environment.